Pre-, Peri-, and Postnatal Factors of Molar–Incisor Hypomineralization in Brazilian Schoolchildren: A Cross-Sectional Study - Karina Kendelhy Santos; Patrícia Gomes Fonseca; Túlio Silva Pereira; Jéssica Madeira Bittencourt; Maria Letícia Ramos-Jorge; Maria Eliza da Consolação Soares; Lívia Guimarães Zina; Izabella Barbosa Fernandes (International Journal of Environmental Research and Public Health, 2026)
To assess the prevalence of molar–incisor hypomineralization (MIH) and identify the associated factors in Brazilian schoolchildren, a representative cross-sectional study was conducted Diamantina, Brazil, with a random sample of 316 (80.8% response rate) children aged 7 to 10 from public and private schools. The presence of MIH was assessed according to the criteria of the European Academy of Pediatric Dentistry (EAPD). Sociodemographic data and data related to the prenatal, perinatal, and postnatal periods, as well as child health, were obtained through a questionnaire sent to caregivers. Descriptive analyses and adjusted and unadjusted Poisson regression were performed, accounting for the sample weights, using Stata software (version 16.1). The prevalence of MIH was 21.2%. The adjusted model showed that children admitted to the neonatal intensive care unit (NICU) were 2.28 times more likely to have MIH (95% CI: 1.34–3.90). The present study identified a high prevalence of MIH among children aged 7 to 10 years in Brazilian schoolchildren. Children who were admitted to the NICU had a higher prevalence of MIH than those who did not. Given the cross-sectional design, study sample and regional context, these findings should be interpreted as associations rather than evidence of causal relationships.